You are on page 1of 3

George Basdekis

Vanessa Pappa

Sum Of Squares
.
.
. .
.

, , 2013

1.

m
a4 + n
a2 b2 + p
a3 b + g
ab3 (m + n + p + g)
a2 bc 0
a, b, c .
, m > 0 3m(m + n) p2 + pg + g 2 .
.
(
)
(
)
(
)

m
a4
a2 b2 + (m + n)
a2 b2
a2 bc + p
a3 b
a2 bc +
(
)

3
2
+g
ab
a bc 0.

a4

a 2 b2 =

1 2
(a b2 )2 .
2

a3 b
a2 bc =
b3 c
a2 bc =
bc(b2 a2 ) =
bc(a2 b2 )

1 2
=
bc(a2 b2 ) +
(a b2 )(ab + bc + ca)
3
]
[

1
2
2
=
(a b ) (ab + bc + ca) bc
3

1
=
(a2 b2 )(ab 2bc + ca)
3

ab3
a2 bc =
bc3
a2 bc =
bc(c2 a2 )

=
ca(a2 b2 )

1 2
=
ca(a2 b2 )
(a b2 )(ab + bc + ca)
3
]
[

1
2
2
=
(a b ) ca (ab + bc + ca)
3
1 2
=
(a b2 )(ab bc + 2ca).
3

(1)

(2)

(3)

(4)

George Basdekis

Vanessa Pappa

,
(
)
(
)

p
a3 b
a2 bc + g
ab3
a2 bc =
p 2
g 2
=
(a b2 )(ab 2bc + ca) +
(a b2 )(ab bc + 2ca)
3
3
1 2
=
(a b2 )[p(ab 2bc + ca) + g(ab bc + 2ca)]
3
1 2
=
(a b2 )[(p g)ab (2p + g)bc + (p + 2g)ca].
3

, [(p g)ab (2p + g)bc + (p + 2g)ca]2



(
)

[(p g)ab (2p + g)bc + (p + 2g)ca]2 = 6(p2 + pg + g 2 )


a2 b2
a2 bc
(5)
(1) (2), (3), (4), (5)

m+n
m 2
(a b2 )2 +

[(p g)ab (2p + g)bc + (p + 2g)ca]2


2
2
2
6(p + pg + g )
1 2
+
(a b2 )[(p g)ab (2p + g)bc + (p + 2g)ca] 0
3
,
(
)
]2
m+n
1 [
1
2
2
3m(a b ) + [(p g)ab (2p + g)bc + (p + 2g)ca] +

18m
6(p2 + pg + g 2 ) 18m

[(p g)ab (2p + g)bc + (p + 2g)ca]2 0



]2
1 [
3m(a2 b2 ) + [(p g)ab (2p + g)bc + (p + 2g)ca] +
18m
3m(m + n) (p2 + pg + g 2 )
[(p g)ab (2p + g)bc + (p + 2g)ca]2 0.
2
2
18m(p + pg + g )
m > 0 3m(m + n) p2 + pg + g 2
.

1. a, b, c ,
(a2 + b2 + c2 )2 3(a3 b + b3 c + c3 a).
.

a4 + b4 + c4 + 2(a2 b2 + b2 c2 + c2 a2 ) 3(a3 b + b3 c + c3 a) 0.
m = 1 > 0, n = 2, p = 3, g = 0 3m(m + n) (p2 + pg + g 2 ) = 9 9 = 0
.

2. a, b, c
a4 + b4 + c4 + ab3 + bc3 + ca3 2(a3 b + b3 c + c3 a).

George Basdekis

Vanessa Pappa

.
m = 1 > 0, n = 0, p = 2, g = 1 3m(m + n) (p2 + pg + g 2 ) = 3 3 = 0
.

3. a, b, c r

a4 + b4 + c4 + (3r2 1)
a2 b2 + 3r(1 r)
a2 bc 3r
a3 b.
.
m = 1 > 0, n = 3r2 1, p = 3r, g = 0 3r(r 1) = m+n+p+g.
3m(m + n) (p2 + pg + g 2 ) = 9r2 9r2 = 0 .

.
1. a, b, c

a4 + b4 + c4 + ( 3 1)abc(a + b + c) 3(a3 b + b3 c + c3 a).


2. a, b, c
7(a4 + b4 + c4 ) + 10(a3 b + b3 c + c3 a)

17
(a + b + c)4 .
27

3. a, b, c
a(a + b)3 + b(b + c)3 + c(c + a)3

8
(a + b + c)4 .
27

4. a, b c.
1
a4 + b4 + c4 + (ab + bc + ca)2 2(a3 b + b3 c + c3 a).
3